Balanced Score Card (BSC) sebagai Alternatif Pengukuran Kinerja Lembaga Pendidikan - Julaiha, Siti (Dinamika Ilmu: Jurnal Pendidikan, 2011)
Educational institutions can function well if the its performance can be measured clearly. Educational institutions should be empowered towards optimal empowerment, by developing schools with strategic planning, a vision and mission, an independent school, empowering the community by many efforts to increase the role and participation of the community through school committees. To make schools as an education institution in high quality, it needs to be evaluated and controlled. The School achieved can be said that the institution is measurable. One alternative is offered in measuring the performance of schools is known by the Balanced Scorecard (BSC). Balanced Scorecard was introduced by Robert Kaplan and David Norton by understanding the school's mission and strategy into objectives and measures, which are arranged in four perspectives, namely financial perspective, customer perspective, internal business perspective and the perspective of learning.